Sex differences in the association between dietary choline intake and total bone mineral density among adolescents aged 12–19 in the United States - Gong, Hongyang; Jiang, Jiecheng; Choi, Seok; Huang, Shaoqun (Frontiers in Nutrition, 2024)
Background: While prior research has established a correlation between dietary choline intake and bone density in the elderly, the relationship in adolescents remains ambiguous. This study seeks to examine the association between dietary choline intake and bone density in American adolescents. Methods: Data from the National Health and Nutrition Examination Survey (NHANES) for 2005 to 2018 were used in this study, encompassing participants aged 12 to 19 years. The relationship between dietary choline intake and bone density was assessed using multivariate linear regression models and restricted cubic spline (RCS) models. Subgroup analyses were also performed to investigate differences across various subgroups. Results: 3,800 participants with an average age of 15 years were included in this study. After adjusting for relevant confounding factors, a positive correlation was observed between dietary choline intake and total bone density in adolescents (95% CI: 0.03-0.17, p=0.010). Gender-specific analysis indicated a significant positive correlation between dietary choline intake and total bone density in males (95% CI: 0.07-0.23, p<0.001), while no significant correlation was found in females (95% CI: -0.19-0.09, p=0.500). The stratified analysis revealed that the positive association was more pronounced in males and non-Hispanic whites (interaction p<0.05). The restricted cubic spline model demonstrated a linear positive correlation between dietary choline intake and total bone density.This study demonstrates that dietary choline intake levels are positively correlated with bone density in adolescents, with this association being specific to males.